Comparing the Effects of Whole-Body Cryotherapy and Swimming in Cold Water Winter Swimming on Chosen Morphological and Biochemical Blood Indices and Factors Released by Brown Adipose Tissue - Aneta Teległów; Bartłomiej Ptaszek; Szymon Podsiadło; Mateusz Mardyła; Jakub Marchewka; Marcin Maciejczyk (Rehabilitacja Medyczna, 2022)
Introduction: Whole-body cryotherapy and winter-swimming are applied to induce physiological, organ-related and systemic defence responses that are beneficial and effective in maintaining or restoring human body homeostasis.Objective: The aim of the study was to evaluate blood morphological and biochemical indices in men and women exposed to whole-body cryotherapy and winter swimming.Materials and methods: Fasting blood samples were collected into vacuum tubes from the ulnar vein of all participants (n=70). This was done before beginning and after completing the 20 whole-body cryotherapy sessions (women n=15, men n=15), as well as at the beginning (November) and end of the winter swimming season (April) (women n=15, men n=15), and in the control group (women n=10, men n=10). Blood morphological and biochemical indicators as well as brown adipose tissue were determined at the Blood Physiology Department of the Central Research and Development Laboratory University of Physical Education in Krakw, and at the Department of Analytics and Clinical Biochemistry of the Krakw Unit of Maria Sklodowska-Curie National Research Institute of Oncology.Results: In both sexes included in the study, both whole-body cryotherapy and winter swimming protocols induced changes in selected peripheral blood morphological and biochemical indices, mainly in blood count, proteinogram and chloride concentrations. The increase in brown adipose tissue-released FGF-21 (fibroblast growth factor-21) under the influence of whole-body cryotherapy occurred in females. In contrast, no statistically significant changes were found for Nrg4. Both whole-body cryotherapy and winter swimming resulted in decreased values of red blood cells, haemoglobin and iron, with sex-dependent variation.Conclusions: Cold in the form of whole-body cryotherapy, similarly to winter bathing, affects changes in blood morphological and biochemical parameters, while the release of FGF21 in brown adipose tissue was noted only after whole-body cryotherapy.